The role of the bone marrow in bovine trypanotolerance. 1. Changes in blood and bone marrow in Trypanosoma congolense-infected cattle - Logan-Henfrey, L.L.; Anosa, V.O.; Wells, C.W. (Springer, 1999)
This study compared the changes in the bone marrow (BM) of five trypanotolerant N'Dama cattle with those of four trypanosusceptible Boran cattle during trypanosome infection. In the early parasitaemic phase, from 12 to 21 days postinfection (DPI), tsetse transmitted primary Trypanosoma congolense IL 1180 infection induced parasitaemia, slight depression in packed cell volume (PCV), marked leucopenia due to lymphocytopenia and eosinopenia, and thrombocytopenia which were of similar intensity in Boran and N'Dama cattle. However, from 28 DPI until the end of the experiment on 112 DPI, the parasitaemia was higher in the Boran than in the N'Dama. Severe anaemia and leucopenia characterised by lymphopenia, neutropenia, eosinopenia and monocytopenia persisted in Boran cattle. In contrast, the PCV values dropped gradually in N'Dama cattle and from 77 DPI recovered slowly to values just below preinfection levels by 112 DPI. The total and differential leucocyte counts of the N'Dama cattle stabilised at approximately two thirds of preinfection values between 28 and 112 DPI, and were double those of the Boran. Marked thrombocytopenia occurred in both breeds. The anaemia was initially macrocytic hypochromic but terminally became microcytic hypochromic in both breeds. Light and electron microscopic studies of sequential biopsies of the BM of these animals showed that the BM response was the key to these differences between the N'Dama and Boran. The biopsies of the BM of the N'Dama cattle were hypercellular (scored 4.5 ± 1.0 compared to 4.0 for controls) with mild hyperplasia of erythroid cells and mild hypoplasia of myeloid cells from 28 to 112 DPI, endowing the animals with higher haemopoietic potential that enabled them to replace most lost cells. In contrast, the Boran cattle had hypocellular (scored 2.4 ± 1.1) BM biopsies with relative erythroid hyperplasia and myeloid hypoplasia, resulting in low capacity of cell replacement manifested as severe unremitting anaemia and leucopenia. The BM of both breeds showed moderate hyperplasia of cells of the mononuclear phagocyte system. Therefore, this study showed, for the first time, that BM response is a key determinant factor of trypanotolerance as it determines the animal's capability for blood cell regeneration.